2022
DOI: 10.3389/fmicb.2022.1040056
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the active ingredients and pharmacological mechanisms of the oral intake formula Huoxiang Suling Shuanghua Decoction on influenza virus type A based on network pharmacology and experimental exploration

Abstract: ObjectiveTo investigate the active ingredients, underlying anti-influenza virus effects, and mechanisms of Huoxiang Suling Shuanghua Decoction (HSSD).Materials and methodsThe therapeutic effect of HSSD were confirmed through the survival rate experiment of H1N1-infected mice. Then, the HSSD solution and the ingredients absorbed into the blood after treatment with HSSD in rats were identified by UPLC/Q-TOF MS, while the main contents of ingredients were detected by high performance liquid chromatography (HPLC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Several herbal tonics used in TCM have shown to enhance immunity with little or no toxicity or side effects, and may potentially be used as vaccine adjuvants to promote the secretion of immune-activating factors, activate B cells and T cells, and enhance the body’s humoral and cellular immunity ( 25 ). Our previous research showed that HSSD may aid the treatment of influenza A virus infection by eliciting anti-inflammatory and immunoregulatory effects ( 18 ). Our proof-of-concept study in mice immunized with SARS-CoV-2 S-RBD recombinant protein showed that HSSD supplementation significantly enhanced serum anti-RBD IgG titers, increased the percentage of CD4 + T cells and boosted the secretion of related cytokines, and regulated adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several herbal tonics used in TCM have shown to enhance immunity with little or no toxicity or side effects, and may potentially be used as vaccine adjuvants to promote the secretion of immune-activating factors, activate B cells and T cells, and enhance the body’s humoral and cellular immunity ( 25 ). Our previous research showed that HSSD may aid the treatment of influenza A virus infection by eliciting anti-inflammatory and immunoregulatory effects ( 18 ). Our proof-of-concept study in mice immunized with SARS-CoV-2 S-RBD recombinant protein showed that HSSD supplementation significantly enhanced serum anti-RBD IgG titers, increased the percentage of CD4 + T cells and boosted the secretion of related cytokines, and regulated adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In our previously study, four compounds of HSSD were identified by the HPLC profile, including chlorogenic acid, caffeic acid, scutellarin, and rosmarinic acid, and the contents of two signature ingredients in the HSSD were determined by HPLC method as chlorogenic acid (0.63 mg/g), and hesperidin (3.13 mg/g), respectively. More details on the ingredients of HSSD were published previously ( 19 ). Product standard code of HSSD was GB/T 29602, and its Production License Number was No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation